Lessons learnt from a birthday party: a Bacillus cereus outbreak, Bari, Italy, January 2012 - Domenico Martinelli; Francesca Fortunato; Silvio Tafuri; Vanessa Cozza; Maria Chironna; Cinzia Germinario; Biagio Pedalino; Rosa Prato (Istituto Superiore di Sanità, 2013)
INTRODUCTION: Bacillus cereus, a ubiquitous bacterium, can be isolated in various starchy food items, causing both emetic and diarrhoeal disease. The real burden of B. cereus outbreaks is actually poorly known in Italy. We report a B. cereus foodborne outbreak that occurred in a pub in Bari (Italy) on January 22nd 2012 during a birthday party, promptly reported by the pub owner. MATERIALS AND METHODS: Between January 22nd and 24th 2012, we performed a retrospective cohort study among the guests of the party to identify risk factors associated with illness. Leftovers of different meals were available for microbiological analysis. Faecal specimens were collected from cases. RESULTS: A total of 12 cases among the 13 customers (attack rate: 92%) were reported. All cases had consumed basmati rice and sweet and sour vegetables (aetiological fraction: 100%). B. cereus was isolated from both basmati rice served during the party and faecal specimens. DISCUSSION: The close collaboration between the pub owner and the public health officers and the possibility to test food leftovers and stool samples contributed to prevent further cases.